New naphthopyranone glycosides from Paepalanthus vellozioides and Paepalanthus latipes - Vilegas, Wagner [UNESP]; Dokkeddal, A. L.; Piacente, S.; Rastrelli, L.; Pizza, C. (Amer Chemical Soc, 1999)
Three new compounds-3,4-dihydro-10-hydroxy-7-methoxy-3-(R)-methyl-1H-3,4-dihydronaphtho-]2,3c]pyran-1-one-9-O-beta-D-glucopy ranoside (1), 3,4-dihydro-10-hydroxy-7-methoxy-3-(R)-methyl-1H-3,4-dihydronaphtho-[2,3c]-pyran-1-one-9-O-beta-D-glucopyranosyl-(1-->6)-glucopyranoside (2), and 3,4-dihydro-10-dihydroxy-7-methoxy-3-(R)-methyl-1H-3,4-dihydronaphtho-[2,3c]-pyran-1-one-9-O-beta-D-allopyranosyl (1-->6)-glucopyranoside (3)-were isolated from the leaves of Paepalanthus vellozioides and Paepalanthus latipes and characterized by spectrometric methods, mainly electrospray mass spectrometry and 1D and 2D NMR experiments. These unusual glycosylated dihydronaphthopyranones may serve as taxonomic markers of the genus Paepalanthus, since these compounds were not detected in other genera belonging to the Eriocaulaceae family.